Pembentukan Karakter Peduli Sosial Dan Tanggung Jawab Pada Ekstrakurikuler Dokter Kecil (PMR) Di MIM Karanganyar - Hutami Nosa Apriastuti; Arief Cahyo Utomo (Elementary Teacher Education Program, Majalengka University, 2023)
Character education is needed to shape students to have good character and be useful for others. In this regard, this study intends to explain the role of the little doctor's extracurriculars in the formation of the character of social care and responsibility, as well as the supporting and inhibiting factors in the formation of the character of social care and responsibility. This research is a qualitative descriptive study using data collection techniques in the form of interviews, observation, and documentation. The results of this study show that the character of social care forms students with attitudes including: a) treating other people politely; b) tolerance for differences; c) willing to listen to others; and d) willing to share, while the character of responsibility forms students with attitudes including: a) understanding their own rights and obligations; b) play an active role in the activities carried out; c) accept the risk of every activity carried out; and d) carry out tasks without orders. The character of social care and responsibility can be formed through various little doctor activities, namely routine Saturday and Monday activities, participating in activities outside school like camping, social service, and quiz competition. From these various activities there are supporting factors in the formation of a socially caring and responsible character including: 1) facilities and infrastructure; 2) Routinely participate in activities outside of school; and 3) There is cooperation with the puskesmas. While the inhibiting factor in the formation of the character of social care and responsibility is the implementation time extracurricular limited.